Preparation of nano-platinum and its catalytic activity toward methanol oxidation and oxygen reduction - 黄幼菊 戴宏海 李伟 张庆龙 赵灵智 李伟善 (Transactions of Nonferrous Metals Society of China, 2007)
Nano-scale platinum catalysts were prepared on a glass carbon electrode by cyclic voltammetry. The surface morphology and active area of the catalysts, and their catalytic activity toward methanol oxidation and oxygen reduction were studied by SEM, linear and cyclic voltammetry. The result shows that the diameters of global Pt particles are affected by the scan rate of cyclic voltammetry： the faster the scan rate is, the smaller the diameters of Pt particles are. The size of the nano-scale platinum catalysts has different effects on their catalytic activity toward oxygen reduction and methanol oxidation： the catalyst with a size of 100 nm shows its best activity toward methanol oxidation, but the catalyst with a size of 65 nm shows its best activity toward oxygen reduction.